Stanford’s ME310 Course as an Evolution of Engineering Design - Carleton, T.; Leifer, L. (Cranfield University Press, 2009)
ME310 is a radical course that has been taught at Stanford University since 1967. The year-long course is a graduate level sequence in which student teams work on complex engineering projects sponsored by industry partners. Student teams complete the design process from defining design requirements to constructing functional prototypes that are ready for consumer testing and technical evaluation. This paper presents the first longitudinal study of ME310 and characterizes the course in terms of nine eras, each with distinctive teaching philosophies and class dynamics. By looking at one engineering design course in its entirety, a rough parallel is gained of how the field of engineering design itself has evolved over the last forty years. Data for this study was drawn from 80 surveys, 28 interviews, and 42 years of historical university enrollment records, course archives, and course bulletins.
Organised by: Cranfield University
Keywords: Engineering Design Education; Problem-Based Learning; Innovation; Immersion; Simulation